Analysis of growth and exploitation rate of Eleutheronema tetradactylum in the Bengkalis waters , Bengkalis Regency - Nafisah Nafisah; Eni Sumiarsih; Nul El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACKEleutheronema tetradactylum isan important economic valued fish in the Bengkalis waters. Due to the high demand of consumers, the fish is highly exploited and it negatively affects the fish population. This study was done in the Bengkalis waters on May to July 2020 and purposed to understand the length frequency distribution, determine the growth parameters, mortality rate and the rate of exploitation in order to provide appropriate management model for that fish resource. Data were analysis by a ELEFAN I method (Electronic Lenght Frequencys Assesment Tool) from the FISAT II (FAO-ICLARM Fish Stock Assesment Tool) software. E. tetradactylumcaptured were 78 samples, the length frequency distribution of the female fish were ranged from 75 to 154 cm TL. The growth pattern of the fish was allometric negative. The Von Bertalanffy growth equation shown that the coefficient (K) 1.01 with infinitive length (L∞) 151.2 cm and t0 -0.2115 per year. The total mortality rate (Z) of the fish was 3.43 per year at the rate of natural mortality (M) 1.14 per year, while mortality rate due to fishing (F) 2.30 per year and the exploitation rate was 0.67 per year. The value of the exploitation rate has exceeded the value of the optimum exploitation that was 0.5.Keywords:Allometric negative, FISAT II, Infinitive Length, Mortality,Von bertalanffy.